Reinterpretation of the Words Falyanzur and Tha'am in Qs 'Abasa Verse 24 to Build Public Nutrition Awareness - Hanifah, Annisa Nur; Sowaidi, Belqes Al; Nirwana AN, Andri (Universitas Muhammadiyah Surakarta, 2025)
The Quran contains the concept of balanced nutrition in several of its verses, including in Surah Al-Baqarah 168, Surah Al-A'raf verse 31 and Surah Abasa verse 24. The interpretation of Surah Abasa verse 24 and its relation to nutrition there are still differences among scholars of interpretation. This research uses a qualitative approach, this type of research is descriptive analytical. The term linguistics refers to the science that studies language and analyzes it scientifically. The reinterpretation theory used in this research is Abdullah Saeed's theory. The word nazara and its derivations have a dominant meaning related to the activity of the five senses, namely vision. However, not only limited to physical observation, this seeing activity also involves the heart and mind, which makes it more than just ordinary observation. The word tha'am and its various derivatives are mentioned 48 times in the Quran, and cover various aspects related to food, including the type, method of consumption, and its role in daily life. In this study, researchers want to provide a reinterpretation of the 2 words so that the meaning of the verse becomes an order to humans to pay attention to the nutritional content of their food. The order that humans pay more attention to their food patterns and portions so as to avoid various diseases due to unbalanced nutrition.